Zirconia crowns for oral rehabilitation in pediatric dentistry: a new aesthetic alternative - Abal-Perleche, Dessire (2018)
For decades, stainless steel crowns have been considered the easiest and most durable restoration. However, due to the poor aesthetics they offer, these crowns are no longer acceptable to patients and/ or their parents. Currently, use of  crowns as a rehabilitative treatment is common and the pediatric dentist requires practical knowledge, which is why innovative aesthetic alternatives such as zirconia crowns have emerged. For this reason, the objective of this article is to offer a clinical guide to the management of zirconia crowns in the anterior and posterior regions of deciduous dentition.